Analisis Kebutuhan Siswa Terhadap Media Pembelajaran Komik Digital Pada Materi Hak Dan Kewajiban Kelas IV SD - dimas; Iis; Wendri (Universitas Islam Nahdlatul Ulama Jepara, 2026)
This study aims to analyze the learning needs of fourth-grade students at UPT SDN Gedongombo 1 for the development of digital comic learning media on the topic of rights and obligations. This study employed a descriptive qualitative approach supported by simple quantitative data. Data were collected through non-participant observation using a 15-indicator observation sheet and semi-structured interviews consisting of 15 questions with the fourth-grade teacher. The study was conducted on January 28, 2026, involving 25 fourth-grade students and one classroom teacher. The findings showed that 10 of the 15 observed indicators (66.7%) were adequately implemented, while 5 indicators (33.3%) indicated problems, particularly in the use of learning media and student engagement. Only 11 students (44%) achieved the Learning Objective Achievement Criteria (KKTP), while 14 students (56%) had not yet achieved the criteria. Interview findings further revealed that learning was still dominated by lectures, textbooks, and worksheets, while available digital facilities such as laptops, LCD projectors, and internet access had not been optimally utilized. Both teachers and students needed learning media that were engaging, contextual, interactive, and capable of stimulating curiosity. Based on these findings, digital comics are considered a relevant potential medium for supporting the teaching of rights and obligations. The results provide a needs-based foundation for the subsequent development of KOMHAK (Digital Comic on Rights and Obligations) as a contextual and interactive learning medium for fourth-grade elementary school students.